1988
DOI: 10.1038/335651a0
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein surface charges in ion binding

Abstract: Protein engineering is a means of probing the role of electrostatic interactions in protein functions; this elegant technique has been applied to the elucidation of electrostatic effects in enzyme catalysis. Here we show how the use of mutant proteins allows the determination of the contributions of individual charges to the free energy of ion binding to proteins. We have investigated the importance of three negatively charged side chains in the binding of Ca2+ to bovine calbindin D9K (ref.2): these are cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 10 publications
3
113
1
Order By: Relevance
“…A similar effect with divalent cations (and negative charges) has been noted in other protein systems (Voordouw et al, 1976;Filimonov et al, 1978;Bashford et al, 1986;Linse et al, 1988;Pantoliano et al, 1988). The effect of phosphate above its second pK, is expected to be essentially the same as sulfate.…”
Section: Effect Of Phosphatesupporting
confidence: 58%
“…A similar effect with divalent cations (and negative charges) has been noted in other protein systems (Voordouw et al, 1976;Filimonov et al, 1978;Bashford et al, 1986;Linse et al, 1988;Pantoliano et al, 1988). The effect of phosphate above its second pK, is expected to be essentially the same as sulfate.…”
Section: Effect Of Phosphatesupporting
confidence: 58%
“…Electrostatic interactions also play a role in the calcium binding properties as has been demonstrated in the case of the intact protein [IO,1 11. This is also true for the fragments.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Ackers et al (1983) have shown that it is generally possible to extract the value of AAG, from individual-site binding isotherms; and estimates of AAG,. for calbindin Dgk are becoming available from spectroscopic and mutagenesis studies (Linse et al, 1991). Finally, it will be shown that the main results of this paper would be the same, even if the macroscopic definition were used.…”
Section: K Kllmentioning
confidence: 88%
“…However, in the more general case of nonidentical binding sites, the 7-dependent term is negative so that AAG, < -RT ln(4K2/K1); in other words, the macroscopic definition provides an upper limit on the value of the microscopic AAG,. (Linse et al, 1988). It is therefore possible that, in systems with nonidentical sites that bind ligands independently (AAG,.…”
Section: K Kllmentioning
confidence: 99%